2018
DOI: 10.1039/c8ra05356a
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects and possible molecular mechanisms of action of fibrauretine fromFibraurea recisaPierre ond-galactose/AlCl3-mediated Alzheimer's disease

Abstract: Fibrauretine from Fibraurea recisa Pierre exhibits ameliorative effects on d-galactose/AlCl3-induced Alzheimer's disease. Its mechanism may involve its antioxidant, anti-inflammatory and anti-apoptotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 66 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…Our results showed that AlCl3 (in ADM group) impaired short term working memory, where spontaneous alternation behaviour (SAP) was reduced. This result supported with Xing et al (2018) and Zghari et al (2018) found that exposure of rat and mice to Al or AlCl3 and D-galactose reduced spontaneous alternation percentage in Y-maze test. While treatment with GS and MO enhanced the reduced SAP and this were in agreement with Kim et al (2017) and Omotoso et al (2018) who reported that red ginseng and ginsenoside moringa olifera increased alternation percent in Y-maze.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that AlCl3 (in ADM group) impaired short term working memory, where spontaneous alternation behaviour (SAP) was reduced. This result supported with Xing et al (2018) and Zghari et al (2018) found that exposure of rat and mice to Al or AlCl3 and D-galactose reduced spontaneous alternation percentage in Y-maze test. While treatment with GS and MO enhanced the reduced SAP and this were in agreement with Kim et al (2017) and Omotoso et al (2018) who reported that red ginseng and ginsenoside moringa olifera increased alternation percent in Y-maze.…”
Section: Discussionsupporting
confidence: 83%
“…There is growing evidence that neuronal apoptosis plays an important role in the pathogenesis of AD [33,34]. Among the other conditions which induce apoptosis, production of reactive oxygen species (ROS), nitric oxide (NO), glucocorticoids and over expression of Bax are known to be major contributory factors for the release of cytochrome c (Cty c) [2,35]. The Bcl-2 family of proteins, which include pro-apoptotic proteins like Bax and anti-apoptotic proteins like Bcl-2, strictly regulates the release of Cyt c [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Surgucheva reported that decreased concentration of Îł-synuclein (Syn G) in retinal ganglion cells (RGC-5) triggers mitochondrial pathway apoptosis via interaction of dephosphorylated Bad protein with pro-survival Bcl-2 family members, such as Bcl-2 and BcL-XL [42]. Activation of upstream caspases, such as caspase-9, will trigger downstream effector caspases, such as caspase-3, which can, in turn, cleave nuclear and cytoskeletal proteins to produce apoptosis [2,43]. For evaluating the extent of apoptosis in the hippocampus of rats exposed to d -gal and AlCl 3 and the protective effects of CA, the expressions of Bcl-2 and caspase-3 were assessed in the present study by RT PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of D-galactose trigger ROS accumulation in the brain, ultimately inducing oxidative stress and the production of advanced glycation end products (AGEs). These changes have been shown to be involved in physiologically aging and in neurodegenerative diseases, such as AD and Parkinson's disease, indicated by the presence in senile plaques and neurofibrillary tangles (28,29). Additionally, the accumulation of ROS activates the mitochondrial apoptotic pathway via cytochrome c release (30) and markedly decreased glutamine synthetase expression in the brain of mice (31).…”
Section: Discussionmentioning
confidence: 99%